Challenges and Impacts of Social Inclusion Libraries on Literacy in South Bengkulu - Hamudy, Moh Ilham A; Rifki, M Saidi; Hayuningtyas, Mukhlisha (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2025)
This study aims to analyze the challenges and impacts of the Social Inclusion-Based Library Transformation Program (TPBIS) on literacy development in South Bengkulu. Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that TPBIS activities often lack alignment with the program’s core objectives, are implemented without strategic planning, and fail to reach diverse community groups. These shortcomings have contributed to low scores in the Community Literacy Development Index and Reading Interest Level. Key challenges include inadequate planning, limited budget, and weak cross-sectoral coordination. Therefore, a clearer understanding of TPBIS objectives, a comprehensive analysis of community needs, and stronger institutional collaboration are necessary to improve program effectiveness and accountability. In this context, the House of Representatives of the Republic of Indonesia (DPR RI), through Commission X, plays a strategic role in ensuring policy effectiveness by overseeing the implementation of TPBIS or similar programs, particularly in ensuring accountability and responsiveness to local needs. Furthermore, DPR RI is expected to encourage increased budget allocations for improving library infrastructure, developing human resource capacity, and fostering synergy among ministries and institutions to support inclusive and sustainable national literacy development.